2018
DOI: 10.1007/s00702-018-1857-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 and complement serum level study in Parkinson’s disease

Abstract: The objective of this study is to assess whether elevation of serum inflammatory markers levels may indicate the progression of clinical impairment in Parkinson's disease (PD) patients. In 47 PD patients, the serum levels of the C3 and C4 part of the complement and Interleukin-6 (IL-6) were measured. The results at baseline and after 2 years were correlated with scales measuring memory, depression, motor symptoms, and quality of life. Patients with higher levels of C3 and C4 at baseline had decreased quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…However, females are more likely to suffer from cognitive disorders, pain symptoms, and depression (Georgiev et al, 2017). PD patients who had higher levels of serum C3 and C4 at baseline and maintained consistently high levels over 2 years had a worse quality of life and memory ability (Veselı et al, 2018). After adjusting for other clinical factors, we found that the serum C3 level was inversely correlated with male gender, age, and the severity of sleep/fatigue problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, females are more likely to suffer from cognitive disorders, pain symptoms, and depression (Georgiev et al, 2017). PD patients who had higher levels of serum C3 and C4 at baseline and maintained consistently high levels over 2 years had a worse quality of life and memory ability (Veselı et al, 2018). After adjusting for other clinical factors, we found that the serum C3 level was inversely correlated with male gender, age, and the severity of sleep/fatigue problems.…”
Section: Discussionmentioning
confidence: 99%
“…Increased inflammatory responses have been described both in the brain and peripheral blood of PD patients (135). Depression correlated with a high serum level of IL-10 (136) and IL-6 (137). High levels of both sIL-2R and TNF-α in blood samples from PD patients were significantly associated with more severe depression and anxiety (119).…”
Section: Depressionmentioning
confidence: 99%
“…These results suggest that non-steroidal anti-inflammatory drugs could perhaps be used to treat major depressive disorders. Interestingly, the increase in IL-6 in childhood enhances the risk of developing depression later in life [243], and there is a relationship between high IL-6 levels and depression in patients with PD [244]. Figure 6 reports the main mechanisms involved in depression.…”
Section: Depressionmentioning
confidence: 99%